The Correlation Between Students’ Reading Anxiety and Their Reading Comprehension in ESP Context - Wijayati, Primardiana Hermilia; Mardianti, Nunung; Murtadho, Nurul (Universitas Negeri Makassar, 2021)
This study aimed to analyze the relationship between reading anxiety and reading comprehension of ESP students in Universitas Muhammadiyah Malang. The participants in this study were 50 first-year Governmental Science students who took intensive reading I. This study used correlational design to analyze the relationship between two variables (Reading anxiety and Reading comprehension). In collecting the data, the English Foreign Language Reading Anxiety Inventory (EFLRAI) questionnaire was used to investigate the level and potential causes of reading anxiety. Moreover, in assembling students' reading comprehension data, the researcher constructed a reading comprehension test specifically for governmental science students. Based on the study results, the non-English department students belong to moderate a level of reading anxiety. Specifically, reading anxiety is divided into three main aspects; top-down reading anxiety, bottom-up reading anxiety, and classroom reading anxiety. It was found out that the most potent sources of reading anxiety were in bottom-up reading anxiety, namely unclear-meaning vocabulary in English written text. Regarding students reading comprehension level, the ESP students have a low reading comprehension score. Besides, the research findings illustrated that there is a negative moderate-strong relationship between reading anxiety and Comprehension of ESP students. In means, the higher anxiety the students have, the lower their comprehension score they obtained. Thus, by knowing this, the teacher should select a carefully teaching method in their ESP classroom to decrease their reading anxiety and encourage them to improve their reading comprehension and deal with their anxiety.